MODEL KETAHANAN KELOMPOK TANI PADA WILAYAH DAN KOMODITAS YANG BERBEDA DI JAWA - Zaim Uchrowi; Amri Jahi; Bunasor Sanim; Sumardjo Sumardjo (Jurnal Penyuluhan, 2006)
The Green Revolutions failure caused many farmer groups to cease their activities, even though they had to fulfill many needs. This situation created a need to develop a model for group survival. With those afore mentioned background, this research was conducted. Data was collected in September and October 2005 involving rice, soybean, corn and vegetables farmer groups in the east, central and west Java. The research findings pointed out that there was a relationship between the group survival and their adaptation, goal attainment, integration and latency functions. The group survival rates were higher in central and east Java than in west Java. Additionally, the vegetable and rice farmer group survival rates were higher than the soybean and corn farmer groups. The adaptation, the goal attainment and the integration functions were more strategic for farmer groups in the west and east Java and also for vegetable farmer groups such as soybean and corn group wereas the strategic function were adaptation and integration.